Depression status as a predictor of quit success in a real-world effectiveness study of nicotine replacement therapy. Issue 1 (30th March 2015) - Zawertailo, Laurie; Voci, Sabrina; Selby, Peter
Abstract: To provide population-level evidence of the role of current depression on smoking cessation treatment success, we conducted a secondary analysis of data obtained from a large cessation study conducted in over 13, 000 smokers. On the basis of self-reported history of depression diagnoses at baseline, participants were divided into four mutually exclusive groups: current/recent depression, recurrent depression, past depression and no depression history. Cessation outcomes were compared among the four groups at 6-month follow-up. Of the 6261 individuals who were consented and attempted to be contacted for follow-up, 4648 (74.2%) had no diagnostic history of depression, 591 (9.4%) had a past history of depression, 759 (12.1%) had a current/recent depression diagnoses, and 263 (4.2%) had recurrent depression (both current and history). Those with recurrent depression were significantly less likely to quit smoking compared to those with no history of depression. In unadjusted analyses, recurrent depression was associated with significantly lower odds of quitting compared to those with either no history or a past history of depression. Current/recent depression was also associated with poorer quit outcomes compared to those with no history of depression. Depressed smokers may benefit from more individualized, in-person approaches to smoking cessation. Highlights: 25% of the sample had a history of depression: past only, current only, or both current and past (recurrent). Both current and recurrent depression were strong independent predictors of poorer smoking cessation outcome. Those with current/recent depression reported quit rates higher than those with recurrent depression. Past history of depression predicted quit rates higher than current/recent depression but lower than no history of depression.